Serum interleukin-8 reflects tumor burden and treatment response across malignancies of multiple tissue origins - Sanmamed, Miguel F. (2014)
Purpose: Interleukin-8 (IL8) is a chemokine produced by malignant cells of multiple cancer types. It exerts various functions in shaping protumoral vascularization and inflammation/immunity. We evaluated sequential levels of serum IL8 in preclinical tumor models and in patients to assess its ability to estimate tumor burden. Experimental Design: IL8 levelsweremonitored by sandwich ELISAs incultured tumor cells supernatants, tumor-xenograftedmice serum, and in samples from126 patients with cancer. Wecorrelated IL8 serumlevels with baseline tumor burden and with treatment-induced changes in tumor burden, as well as with prognosis. Results: IL8 concentrations correlated with the number of IL8-producing tumor cells in culture. In xenografted neoplasms, IL8 serum levels rapidly dropped after surgical excision, indicating an accurate correlation with tumor burden. In patients with melanoma (n = 16), renal cell carcinoma (RCC; n = 23), non-small cell lung cancer (NSCLC; n = 21), or hepatocellular carcinoma (HCC; n = 30), serum IL8 concentrations correlated with tumor burden and stage, survival (melanoma, n = 16; RCC, n = 23; HCC, n = 33), and objective responses to therapy, including those to BRAF inhibitors (melanoma, n = 16) and immunomodulatory monoclonal antibodies (melanoma, n = 8). IL8 concentrations in urine (n = 18) were mainly elevated in tumors with direct contact with the urinary tract. Conclusions: IL8 levels correlate with tumor burden in preclinical models and in patients with cancer. IL8 is a potentially useful biomarker to monitor changes in tumor burden following anticancer therapy, and has prognostic significance.